Strategic Environmental Assessment : Improving Water Resources Governance and Decision Making - World Bank (Washington, DC, 2012)
The Sustainable Development Network (SDN) calls for elevating the environment into upstream processes such as policy, programmatic, and investment dialogue. In its 2002 environment strategy, the Bank committed to use strategic environmental assessments (SEAs), an environmental planning tool for improving decision-making at the strategic level of decision-making, policies, legislation, strategies, plans, and programs (PLSPP), and as a process for improving public policy design and good governance of natural resources. SEAs share many concepts and characteristics as integrated water resources management (IWRM), the accepted paradigm for efficient, equitable, and sustainable management of water resources since the 1990s. IWRM recognizes the dual nature of the environment as both a water using sector and a provider of services that maintains water resources for all sectors. The overall goal of this report is to help water resources and environment professionals use SEAs to effectively implement the principles of IWRM. It recommends a framework for expanding use of SEAs to mainstream environmental considerations in water resources policy, legislative and, institutional reforms, planning and development lending decision-making as well as for enabling adaptation in the water sector.